Micro‐morphological, environmental and phytochemical investigation of herbal medicines by using LM and SEM: A quality control tool. Issue 5 (24th January 2019) - Zafar, Muhammad; Ahmad, Mushtaq; Sultana, Shazia; Lubna,; Amin, Adnan; Naseer, Hafiz Muhammad; Jamal, Zafar; Abidin, Sheikh Zain Ul; Mehmood, Sajid; Khan, Amir Shehzad
Abstract: The use of quality control tool for authentication of Jadwar ( Delphinium denudatum Wall. ex Hook.f. & Thomson), a folk herbal drug used for the treatment of different ailments, was studied. People face problems of adulteration for this drug at global, regional, national and local levels. Two different plant species are commercially marketed in the Indo‐Pak Subcontinent under the same trade name of Jadwar. One is D. denudatum Wall. ex Hook.f. & Thomson and the other is Aconitum heterophyllum Wall. ex Royle. To focus on this problem, a marketable available drug sample of Jadwar was authenticated by using basic microscopy tools (LM) and advanced chemo‐taxonomic markers. Authentication, quality and standardization of this drug was achieved using morphology, organoleptography, UV and IR analyses, scanning electron microscopy of pollen and anatomical investigations. The techniques used for authentication marked the clear difference between the studied plants. Microscopic studies, chemotaxonomic investigation and other techniques used in this project provided the basis for the authentication of this species. Abstract : Micro‐morphological investigation using LM and scanning electron microscopy revealed clear difference between both the herbal drug sources. The pollen of Delphinium denudatum is circular in polar view with scabrate sculpturing where as in Aconitum heterophyllum pollen is circular to inter semi‐angular in polar view, scabrate sculpturing with uniformly distributed over the tectum. Trichomes are different in both the herbal drug sources. Thin layer chromatography (TLC) of roots extract of D. denudatum under UV displays the manifestation of three minor flavonols, whereas roots of A. heterophyllum express the manifestation of four minor flavonols and a phenolic acid. Macro and micro‐morphological studies and other techniques used in this project provided the basis for the authentication of the herbal drug.